Hubungan Kecerdasan Emosional dengan Stres Kerja Perawat di Ruang Rawat Inap Akasia, Cemara dan Cendana Rumah Sakit Dr. Bratanata Kota Jambi - Rani Rizma Al Fatiha h; Yusnilawati Yusnilawati; Indah Mawarti (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: Jobs related to hospitals or health are often exposed to high work stress, namely nurses. Nurses who experience work stress show negative emotional responses. The negative impact of increased work stress and low emotional intelligence on nurses has an impact on the quality of health services. Therefore, when a nurse is exposed to work stress and low emotional intelligence, her performance in providing nursing services will decrease, which in turn will get complaints from patients. Prolonged job stress can contribute to nurse burnout, increased dropout rates, and decreased job satisfaction. In the long term, this can affect nurse retention and reduce the availability and quality of the nursing workforce. Methods: Quantitative research with a correlational type of research using Cross Sectional. Sampling using the Total Sampling approach totaling 46 nurses. Data analysis using Univariate Analysis and Bivariate Analysis. Results: 1) 56.52% emotional intelligence in nurses at Dr. Hospital. Bratanata Kota Jambi is categorized as low and 43.48% is categorized as high; 2) 54.35% work stress on nurses at Dr. Hospital. Bratanata Kota Jambi is categorized as high and 45.65% is categorized as low; 3) There is a relationship between emotional intelligence and work stress on nurses in the inpatient rooms of Akasia, Cemara and Cendana at Dr. Hospital. Bratanata Jambi City in 2022 with a Spearman correlation value of -0.869. That is, high emotional intelligence, the work stress experienced by nurses will be low. Conclusion: There is a relationship between emotional intelligence and work stress of nurses in the Inpatient Room of Akasia, Cemara and Cendana Dr. Jambi City Bratanata Hospital. It is hoped that the hospital can provide various programs for nurses not to experience high stress, and can increase the emotional intelligence of nurses to reduce work stress with training for nurses such as Gathering which can reduce nurse work stress.